Chronic corticosterone treatment enhances extinction-induced depression in aged rats - Huston, Joseph P.; Komorowski, Mara; Silva, Maria A. De Souza; Lamounier-Zepter, Valeria; Nikolaus, Susanne; Mattern, Claudia; Müller, Christian P.; Topic, Bianca (Hormones and Behavior, 2016)
Withdrawal and avoidance behavior are common symptoms of depression and can appear as a consequence of absence of reward, i.e. extinction-induced depression (EID). This is particularly relevant for the aged organism subjected to pronounced loss of former rewards. Avoidance of the former site of reward and increased withdrawal into a distant compartment accompany extinction of food-rewarded behavior in rodent models. During extinction, behavioral markers for re-learning dissociate from indicators of extinction-induced depression. Here we examined the effect of a chronic treatment with corticosterone (CORT), a well-known inducer of depression-related behavior, on EID in adult and aged rats. Adult (3-4months) and aged (18months) male rats were treated with CORT via drinking water for 3weeks prior to extinction of a cued food-reward task. CORT treatment increased the distance from the site of reward and decreased goal tracking behavior during extinction, especially in the aged rats. Plasma hormone levels measured before and after restraint stress showed a decline in basal ACTH- and CORT-levels after chronic CORT treatment in aged animals. The treatment significantly impaired the HPA-axis activation after acute stress in both, adult and aged animals, alike. Altogether, these findings show an enhancement of EID after chronic CORT treatment in the aged organism, which may be mediated by an impaired HPA-axis sensitivity. These findings may have special relevance for the investigation of human geriatric depression.
EVALuna2:23754